PENGARUH KUALITAS LAYANAN LOYALITAS PELANGGAN DAN HARGA TERHADAP MINAT BELI DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVEENING PADA TOKO AIR MINUM ADINDA JAYA DI SITUBONDO - Agustinus Weri Lolo; Riska Ayu Pramesthi; Riza Rachman (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The development of the business world today is very promising and at the same time presents new business challenges for companies operating in Indonesia. Each company is competing to expand its product market to gain profit, which ultimately triggers competition between companies. Business development is an important factor for companies in facing competition in order to remain in existence in Indonesia and be able to control market share and survive from competitor pressure. The main thing that underlies a company in maintaining the existence of its products is the right strategy in facing the dynamics of competition. The purpose of this study is to analyze and test the Influence of Service Quality, Customer Loyalty and Price on Purchase Intention with Consumer Satisfaction as an Intervening Variable. Analysis and hypothesis testing in this study using the Partial Least Square Structure Model (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 Application, Service quality has a positive but insignificant effect on Consumer Satisfaction, Customer loyalty has a positive but insignificant effect on Consumer Satisfaction, Price has a significant positive effect on Consumer Satisfaction, Service quality has a significant positive effect on Purchase Intention, Customer loyalty has a positive but insignificant effect on Purchase Intention, Price has a significant positive effect on Purchase Intention, Consumer satisfaction has a significant positive effect on Purchase Intention, Service quality has a negative but insignificant effect on Purchase Intention through Consumer Satisfaction, Customer loyalty has a negative but insignificant effect on Purchase Intention through Consumer Satisfaction, Price has a significant positive effect on Purchase Intention through Consumer Satisfaction,